Morphological peculiarities of revascularization of perifocal areas of brain infarction - S. I. Tertyshnyi; О. О. Voloshanska; А. М. Serheieva (Patologìâ)
Aim. To study pathomorphological signs of revascularization of perifocal areas of brain infarction in the dynamics of the acute period of the disease.